Life Between Patches: Incorporating Microbiome Biology Alters the Predictions of Metacommunity Models - Miller, Elizabeth T.; Bohannan, Brendan J. M. (Frontiers in Ecology and Evolution, 2019)
Although most models conceptualize a metacommunity as a collection of habitat patches embedded in a matrix that is not hospitable to life, new applications of metacommunity theory to host-microbiome systems have shown this assumption to be flawed. Frequently the matrix is at least somewhat hospitable to the species that normally reside in the habitat patches. We modify an existing patch dynamic metacommunity model to incorporate the possibility of a hospitable matrix and expand the process of dispersal to include moving out of the patch, surviving/growing in the matrix, and moving into a new patch. With these alterations, we find that it is substantially harder for a dispersal specialist to persist in a system with a hospitable matrix compared to an inhospitable matrix. In addition, we find that the traits required to successfully disperse in the hospitable system are different from those required in the inhospitable system. The difference in dispersal traits in a hospitable environment versus an inhospitable one could be especially of interest to host-microbiome systems where manipulation of the matrix is common practice. For example, ventilation or disinfection of built environments is a common way to change the matrix properties for metacommunities of human or animal-associated microbiomes. We conclude that the qualities of the matrix can have important effects on community assembly, and that relaxing matrix assumptions broadens the range of applications for metacommunity ecology, including its use for host-microbe systems.